Ice palace - Swindells, Robert; Jackson, June (London Puffin books, 1992)
Ivan lives in a land where the winter is dark and fearful. Starjik, King of Winter, steals Ivan's little brother and Ivan braves the bitter cold to find him.
Keywords: English fiction